1981
DOI: 10.1113/jphysiol.1981.sp013580
|View full text |Cite
|
Sign up to set email alerts
|

Effects of calcium and ionic strength on shortening velocity and tension development in frog skinned muscle fibres.

Abstract: SUMMARY1. The influence of Ca2+ concentration and ionic strength on the maximum velocity of shortening (Vmax) and the tension generating capability of frog skinned muscle fibres has been studied at temperatures between 1 and 101C.2. Fibre segments were mounted between a force transducer and servo motor, where they could be viewed and photographed through a microscope. Segments in which the striations became non-uniform during activation were discarded.3. Velocity was obtained as a function of load by stepping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
69
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(88 citation statements)
references
References 25 publications
19
69
0
Order By: Relevance
“…An increase in maximum tension does accompany the left shifts of the curve induced by ionic strength reduction and reduction in phosphate concentration. Similar increases in tension with reduction in ionic strength have been reported by others for skinned fibers (Ashley and Moisescu, 1977 ;Julian and Moss, 1981 ;Gordon et al, 1973 ;Thames et al, 1974) and for intact fibers (April et al, 1968 ;Edman and Hwang, 1977 ;Gordon and Godt, 1970) . We observe a large increase in tension with reduction of phosphate from 7.5 to 0 mM in 5 mM substrate but no such increase in 0.25 mM substrate.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…An increase in maximum tension does accompany the left shifts of the curve induced by ionic strength reduction and reduction in phosphate concentration. Similar increases in tension with reduction in ionic strength have been reported by others for skinned fibers (Ashley and Moisescu, 1977 ;Julian and Moss, 1981 ;Gordon et al, 1973 ;Thames et al, 1974) and for intact fibers (April et al, 1968 ;Edman and Hwang, 1977 ;Gordon and Godt, 1970) . We observe a large increase in tension with reduction of phosphate from 7.5 to 0 mM in 5 mM substrate but no such increase in 0.25 mM substrate.…”
Section: Discussionsupporting
confidence: 69%
“…V. of shortening (Edman and Hwang, 1977) and maximum tension (April and Brandt, 1973) have been reported to increase in intact fibers bathed in hypotonic media. In skinned fibers bathed in media of reduced ionic strength, no increase in Vmaz has been observed, although the maximum tension does increase (Julian and Moss, 1981) . Gulati and Podolsky (1978) argue from their skinned fiber data that some kinetic parameters of the cross-bridge cycle must change with reduction in ionic strength .…”
Section: Discussionmentioning
confidence: 97%
“…Camilleri and Hull determined the parameter values of a Hill-type model to fit the data of rapid front-arm release movements at low muscle activation levels, and found that the model parameter v max (shortening velocity at zero load) in function q(v) deviated considerably from the value determined from the tetanic isovelocity experiments (Camilleri and Hull, 2005). The dependence of v max on the calcium ion concentration was also discussed in the earlier literature (Julian and Moss, 1981;Gordon et al, 2000). To compensate for this model error, v max was parameterized by the muscle activation level in some applications (Otten, 1987;Winters and Stark, 1985), and the resulting models no longer had the decoupled multiplicative structure.…”
Section: Discussion When Does the Multiplicative Structure Hold Or Fail?mentioning
confidence: 99%
“…The structure and parameters of each component function are then determined based on the observed muscle properties and the tension data from isometric and isovelocity experiments. Because of the complexity of muscle dynamics (Gordon et al, 2000;Julian and Moss, 1981;Balnave and Allen, 1996) such models can fail to predict the tension under functionally relevant conditions that are remote from the condition under which the model is developed. Perreault and colleagues modeled the cat soleus muscle and found that the error between the model prediction and data was consistently large for a variety of length change and stimulation patterns; sometimes greater than 50% during large length changes (Perreault et al, 2003).…”
Section: Discussion When Does the Multiplicative Structure Hold Or Fail?mentioning
confidence: 99%
See 1 more Smart Citation